Falling labour share and the anaemic growth in Portugal : a post-keynesian econometric analysis - Alcobia, João (2022)
In recent decades, the labour share has experienced a downward trend in Portugal that has occurred at the same time as a weaker and anaemic growth pattern. This seems to suggest that the fall in the labour share represents an important constraint on Portuguese economic growth, which does not support the orthodox claims around wage restraint policies as a necessary condition to improve macroeconomic performance due to their positive effects on private investment through higher profits and on net exports through lesser unit labour costs and a corresponding rise in competitiveness. This study assesses the relationship between labour share and economic growth by performing a time series econometric analysis focused on Portugal from 1970 to 2020. Findings show that labour share positively impacts economic growth in Portugal, which is in line with heterodox claims and particularly with post-Keynesian economics on the beneficial effects on private consumption played by the growth of wages. Findings also confirm that the Portuguese economy follows a wage-led growth regime instead of a profit-led growth regime; that is, a rise in wages boosts economic growth because its beneficial effect on private consumption more than compensates for a prejudicial effect on private investment and on net exports. The study points out the urgent need to adopt public policies to support the growth of wages to avoid more decades of dismal growth and a new ‘secular stagnation’ in Portugal.